Non-Farm Diversification, Poverty, Economic Mobility and Income Inequality : A Case Study in Village India - Himanshu; Lanjouw, Peter; Murgai, Rinku; Stern, Nicholas (World Bank, Washington, DC, 2013)
This paper assembles data at the all-India level and for the village of Palanpur, Uttar Pradesh, to document the growing importance, and influence, of the non-farm sector in the rural economy between the early 1980s and late 2000s. The suggestion from the combined National Sample Survey and Palanpur data is of a slow process of non-farm diversification, whose distributional incidence, on the margin, is increasingly pro-poor. The village-level analysis documents that the non-farm sector is not only increasing incomes and reducing poverty, but appears as well to be breaking down long-standing barriers to mobility among the poorest segments of rural society. Efforts by the government of India to accelerate the process of diversification could thus yield significant returns in terms of declining poverty and increased income mobility. The evidence from Palanpur also shows, however, that at the village-level a significant increase in income inequality has accompanied diversification away from the farm. A growing literature argues that such a rise in inequality could affect the fabric of village society, the way in which village institutions function and evolve, and the scope for collective action at the village level. Failure to keep such inequalities in check could thus undermine the pro-poor impacts from the process of structural transformation currently underway in rural India.